Charge Density Dependent Mobility of Organic Hole‐Transporters and Mesoporous TiO2 Determined by Transient Mobility Spectroscopy: Implications to Dye‐Sensitized and Organic Solar Cells. (2nd May 2013) - Leijtens, Tomas; Lim, Jongchul; Teuscher, Joël; Park, Taiho; Snaith, Henry J.
<x xml:space="preserve">Abstract</x> Transient mobility spectroscopy (TMS) is presented as a new tool to probe the charge carrier mobility of commonly employed organic and inorganic semiconductors over the relevant range of charge densities. The charge density dependence of the mobility of semiconductors used in hybrid and organic photovoltaics gives new insights into charge transport phenomena in solid state dye sensitized solar cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>